Impact of the rs73598374 polymorphism of the adenosine deaminase gene on platelet reactivity and long-term outcomes among patients with acute coronary syndrome treated with ticagrelor. Issue 196 (December 2020) - Verdoia, Monica; Tonon, Francesco; Gioscia, Rocco; Nardin, Matteo; Fierro, Nicolai; Sagazio, Emanuele; Negro, Federica; Pergolini, Patrizia; Rolla, Roberta; De Luca, Giuseppe; ,
Abstract: Background: The positive interaction of ticagrelor with the metabolism of adenosine has been claimed for the large antithrombotic and antiischemic benefits of this antiplatelet agent in acute coronary syndromes (ACS). Adenosine catabolism is regulated by the activity of the adenosine deaminase enzyme (ADA), for which several polymorphisms have been identified. Therefore, the aim of our study was to explore the impact of the rs73598374 polymorphism of ADA gene on platelet reactivity in ACS patients treated with ticagrelor. Methods: We included consecutive patients receiving ASA and ticagrelor after an ACS and coronary intervention. Platelet reactivity was evaluated by impedance aggregometry at 30–90 days post-discharge. The genetic analysis was carried out by PCR and RFLP. Clinical endpoints were mortality, cardiovascular death, recurrent myocardial infarction or coronary revascularization at the maximum available follow-up. Results: Our population is represented by 464 patients, of whom 33.4% were A-heterozygotes and 6 homozygotes. A-allele carriers showed a greater prevalence of renal failure ( p  = 0.02) and a lower rate of previous coronary artery bypass graft ( p  = 0.03) and statin treatment (p = 0.02). No differences in the mean values of platelet reactivity or HRPR on ticagrelor were found according to the ADA genotype (11.3%vs13.9%, p  = 0.45; adjusted OR[95% CI] = 1.17[0.64–2.14], p  = 0.61). At follow up, patients carrying the A-allele showed a non-significantly lower incidence of ACS and repeated unplanned revascularization, although with no effect on mortality. Conclusions: In the present study the rs73598374 polymorphism of the ADA gene did not affect platelet reactivity or the long-term prognosis in patients with ACS receiving dual antiplatelet therapy with ASA and ticagrelor. Highlights: The ticagrelor- adenosine interaction has been claimed for its benefits in acute coronary syndromes (ACS). Genetic variants of the adenosine deaminase (ADA) enzyme could affect adenosine catabolism and ticagrelor effects We evaluated the impact of the rs73598374 polymorphism of ADA gene on platelet reactivity in 464 ACS patients treated with ticagrelor No differences in platelet inhibition were found according to the ADA genotypes A-allele snon-significantly lowered the incidence of ACS and repeated unplanned revascularizations